The Equilibrium Effects of Campaign Finance Deregulation on U.S. Elections - Cox, Christian (Econometrica, 2026)
The U.S. Supreme Court's 2010 decision in Citizens United v. Federal Election Commission deregulated campaign finance, enabling the rise of a new political action committee (the Super PAC) with broad freedom to raise and spend money. This led to an unprecedented surge in spending in primary and general elections. To evaluate the impact of Super PACs, I estimate a multistage model of political competition using data from U.S. Congressional elections between 2010 and 2020. I find that Super PAC spending by both sides prompts offsetting responses, resulting in limited net equilibrium effects. However, by amplifying the role of donors, Super PACs still have the potential to reshape the electoral landscape.